The Effects of Group Guidance Peer Mentoring Module on Grade Performance of Low Academic Achievement Students in a Higher Education Institution - Mohd, Haizan binti (Journal of Education and Vocational Research, 2015)
This study is to evaluate the effects of group guidance on academic mentoring group intervention among foundation students in Private Higher Education Institutions (PHEIs). Whereas, the objective is to measure the effects of peer mentor group guidance on a group of mentor trained under Peer Mentoring Module for academic achievement of students in the Foundation Engineering Program. A total of forty subjects (mentee) have undergone academic mentoring program with forty trained peer mentors, and subjects are low academic achievement of Engineering Foundation Program students in Universiti Tenaga Nasional (UNITEN) who obtained a Cumulative Grade Point Average (CGPA) below 2:00 points, failed subject Calculus 1 (MATF 115) and did not engage in any other mentoring program. Subjects were grouped in 2 groups; Control and Treatment group for a period of 10 weeks by using control studies, the tests before and after (pre and post-test). Component of grade performance is based on achieving results for Calculus 1. Apart from descriptive statistical analysis, nonparametric test are applied to determine its effectiveness in increasing the average difference for the group. Results showed that subjects in the intervention group experienced a positive improvement over the objectives of the study. Interestingly, treatment group showed a significant difference in performance grade for Calculus 1 with a difference of (M=54.5500, SD=8.1336) with the impact strength of 12%. In summary, the intervention of group guidance on Peer Mentoring Module have contributed positively to the findings of the grade performance of students with low academic achievement who have successfully completed their studies in Private Higher Education Institutions and Public Higher Education Institutions in general.